Sensorimotor rehabilitation : at the crossroads of basic and clinical sciences - Dancause, Numa; Nadeau, Sylvie; Rossignol, Serge, 1942- (Progress in brain research, 2015)
This volume of Progress in Brain Research focuses on Sensorimotor Rehabilitation. This well-established international series examines major areas of basic and clinical research within neuroscience, as well as emerging subfields